The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.sbspro.2015.04.606
|View full text |Cite
|
Sign up to set email alerts
|

A “Mental Health Profile” of Higher Education Students

Abstract: A number of studies seem to confirm a degradation of mental health among students in higher education. By developing a "mental health profile" for these students, the aim is to adequately specify remedial actions and initiatives. A sample of 1031 college students was used. The results found were: the mental health is superior to the general population, but the depressive symptomatology is superior to the normal population; probably 32.1% of young adults are emotionally disturbed; marijuana is the drug preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…The increased demand of student mental health has become a global phenomenon and has reached parliamentary debate in the UK. UK initiatives have widened university participation such that students no longer represent a privileged group of society (Sarmento, ). Through this growing attendance, students are approaching counselling services at an overall higher demand and with more complex mental health needs (Holm‐Hadulla & Koutsoukou‐Argyraki, ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased demand of student mental health has become a global phenomenon and has reached parliamentary debate in the UK. UK initiatives have widened university participation such that students no longer represent a privileged group of society (Sarmento, ). Through this growing attendance, students are approaching counselling services at an overall higher demand and with more complex mental health needs (Holm‐Hadulla & Koutsoukou‐Argyraki, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are eight main functions included in Fig. 2, briefly described as follows [3][4][5]: Software system management. The core functions are software maintenance, changing some or all according to demand change or hardware environment change, this function refers to the provision of software system management applications.…”
Section: Design On Software Processmentioning
confidence: 99%
“…Aside from students' alcohol consumption, indicators of loss of social support were also found to be associated with increased risk for psychiatric disorders (Blanco et al, 2008). It is also interesting to note that some literature surveyed (Deasy at al., 2014;Lee, Maria, Estanislao, & Rodriguez, 2013;Sarmento, 2015) suggested that students with higher levels of depressive symptoms are primarily women.…”
Section: Introductionmentioning
confidence: 99%